Bridging the Gap Transnationally-Coupling Migrants' Informal and Formal Business Activities Through Hybrid Business Models - David, Alexandra; Terstriep, Judith; Elo, Maria (Wiley, 2025)
Multifocal practices allow transnational migrant entrepreneurs (TMEs) to access extended opportunity structures in diverse entrepreneurial ecosystems (EEs). National and regional regulations, customer relations, market demands, networks, and country-specific entrepreneurial statuses facilitate the strategic coupling of informal and formal business structures toward hybrid business models. However, "how" TMEs innovate and develop approaches to build from informal, formal business models in parallel across national borders remains largely underexplored. Our multiple case study presents three Polish-German TMEs who operate on a multifocal basis in different ecosystems. The longitude study of these entrepreneurs illustrates how transnational migrant businesses can change the owners' power dynamics, habitus, and feelings of belonging while counteracting social exclusion and self-discrimination. Our study contributes to the theoretical debate by illuminating the pathway between informality and formality facilitated by migrant entrepreneurs' transnational business models and their multifocal practices, possibly turning into transnational embeddedness in two or more ecosystems.